2016
DOI: 10.1051/0004-6361/201628236
|View full text |Cite
|
Sign up to set email alerts
|

Propeller effect in two brightest transient X-ray pulsars: 4U 0115+63 and V 0332+53

Abstract: Aims. We present the results of the monitoring programmes performed with the Swift/XRT telescope and aimed specifically to detect an abrupt decrease of the observed flux associated with a transition to the propeller regime in two well-known X-ray pulsars 4U 0115+63 and V 0332+53. Methods. Both sources form binary systems with Be optical companions and undergo so-called giant outbursts every 3-4 years. The current observational campaigns were performed with the Swift/XRT telescope in the soft X-ray band (0.5-10… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
113
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(122 citation statements)
references
References 58 publications
8
113
1
Order By: Relevance
“…This transition can be understood in terms of the thermal-viscous instability model as a moment when temperature at the outer radius of the accretion disk reached the critical temperature of ∼ 6500 K causing the decrease of the local viscosity and corresponding a decline of the mass accretion rate onto the compact object (see, e.g., Lasota 2001). This results in the fast decay of the luminosity observed, particularly, from XRPs in the very end of their outbursts (see recent works by Tsygankov et al 2016a;Lutovinov et al 2017). As can be seen from Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This transition can be understood in terms of the thermal-viscous instability model as a moment when temperature at the outer radius of the accretion disk reached the critical temperature of ∼ 6500 K causing the decrease of the local viscosity and corresponding a decline of the mass accretion rate onto the compact object (see, e.g., Lasota 2001). This results in the fast decay of the luminosity observed, particularly, from XRPs in the very end of their outbursts (see recent works by Tsygankov et al 2016a;Lutovinov et al 2017). As can be seen from Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We extracted the XRT light curves using the online XRT data products tool (Evans et al 2007(Evans et al , 2009, 2 which is shown in Figure 1 (red). Detailed analysis of the decay phase is presented by Tsygankov et al (2016a), who focusses on the transition from the direct accretion regime into the propeller state. This transition likely occurred when the decay rate accelerated, causing the sources to decrease rapidly in X-ray luminosity (Figure 1).…”
Section: Observations Analysis and Resultsmentioning
confidence: 99%
“…The 2.5−15 keV spectrum is well described by a single power law with the best-fit photon index Γ ∼ 2.0 ± 0.1, giving χ 2 = 24.3 for 32 degrees of freedom. Tsygankov et al (2016) of the BeXBs 4U 0115+63 and V 0332+53. These authors found that an absorbed blackbody with kT ≈ 0.5 keV described the low-state spectra well.…”
Section: Transition To the Propeller Regimementioning
confidence: 99%
“…For example, a fraction of matter may still leak through the barrier (Doroshenko et al 2011). Alternatively, high-energy radiation may also be detected as a thermal spectrum, which likely originates in the polar caps of the neutron star surface heated during intermittent accretion episodes or by non-uniform cooling of the neutron star surface after a recent outburst (Reig et al 2014;Tsygankov et al 2016). Deep crustal heating, where the crust of the neutron star cools by X-ray emission until it reaches thermal equilibrium, can also account for the emission at quiescence (Brown et al 1998;Wijnands et al 2013).…”
Section: Transition To the Propeller Regimementioning
confidence: 99%